If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -90) = 3x + 2 Reorder the terms: 6(-90 + x) = 3x + 2 (-90 * 6 + x * 6) = 3x + 2 (-540 + 6x) = 3x + 2 Reorder the terms: -540 + 6x = 2 + 3x Solving -540 + 6x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -540 + 6x + -3x = 2 + 3x + -3x Combine like terms: 6x + -3x = 3x -540 + 3x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 -540 + 3x = 2 + 0 -540 + 3x = 2 Add '540' to each side of the equation. -540 + 540 + 3x = 2 + 540 Combine like terms: -540 + 540 = 0 0 + 3x = 2 + 540 3x = 2 + 540 Combine like terms: 2 + 540 = 542 3x = 542 Divide each side by '3'. x = 180.6666667 Simplifying x = 180.6666667
| .05(x)=20 | | -2.1=-0.6u+0.3u | | -2.1=-0.6+0.3 | | (6x-1)+121=180 | | s-2/3=2 | | 12y^2-6y=0 | | 3/2t=-1/3 | | n*2+5=-n-13 | | (3x+9)+132=180 | | -2g-3(7g+6)=-156 | | 1k+9=6k-66 | | g(x)=-2x+13 | | 2=4/w | | -3(3b-2)= | | -5/5i | | 4/5y-20=160 | | 22x=23x-1 | | 8X=7X-21 | | 5-11=-3z | | 7(5x-4)-(5+7x)= | | 4r-p=q | | 12g=24 | | 9(6-5x)-2(3+6x)= | | 5(3x-2)=(2x-1) | | g(x)=3-9x | | 9(8+5m)= | | -8v+3(v+3)=14 | | 4(9x+8)-9(6-3x)= | | (x+4)(x+2)-3=0 | | (8x-4)+92=180 | | f(x)=x-17 | | 5(7x-8)-6(12x-4)= |